Politik Hukum Problematika Keberlakuan UU Cipta Kerja Pasca Putusan Mahkamah Konstitusi No. 91/PUU-XVIII/2020 - Fitria Ningsih (Publikasi Indonesia, 2022)
The problem with the enactment of the Job Creation Law has finally been confirmed by the Constitutional Court by stating that there was a violation of the constitution during the formation of the Job Creation Law. Less aspirational, the method of formation to changing the manuscript into revealed findings. The intention to amend the Manpower Law through the Employment Creation Act is actually not the first time this has been done, since the formation of the Manpower Law has been through many debates. The urgency of this research stems from the controversy over the birth of the Job Creation Law which continues after the Constitutional Court Decision No. 91/PUU-XVIII/2020. The 'conditionally unconstitutional' decision on the Job Creation Law provides intellectual property from legal scholars; Remember, several points of view examine the problem. This legal research uses an approach and approaches to laws and regulations based on primary legal materials, secondary legal materials, and non-legal materials. After it was decided the conditional unconstitutionality of various interpretations was revealed. The attitude of the government and lawmakers continues to implement policies related to labor by referring to the Job Creation Law. The revision of the Law on the Establishment of Legislation is considered as the first step for the legislators to provide a new dress code for the Job Creation Law.